Struktur Latihan Surya Namaskara dalam Mencapai Kesehatan - Ni Ketut Pande Muliartini (Jurnal Yoga dan Kesehatan, 2018)
Asana is different from physical exercise which gives a burden to muscles but is an exercise that pays attention to relaxation and concentration. In this way, the endocrine glands, internal organs and muscles can also be used to perform their functions. Asana has physical and psychological influences that are useful in the recovery of various diseases. The path of āsana sadhana is a step in the eight stages of the Patanjali yoga sutra which is to make our body steady and firm for higher techniques before going to the level of pratyāhara. It turns out that āsanas are not only popular among Hindus, many are favored by other people, this proves that by doing āsana in daily life, the asanas are very beneficial for health life both physical, mental, muscular and social health. Yoga teaches calm in dealing with problems or conflicts that occur between individuals. Yoga is an implementation of ethics in philosophy. Yoga can answer the problem of what causes human happiness. Yoga can be used as an alternative treatment, usually done with breathing exercises, asanas poses and meditation.